Assessing the reaction conditions to mediate the milkfat-soybean oil enzymatic interesterification - De Paula, Ariela Veloso [UNESP]; Nunes, Gisele Fátima Morais; De Castro, Heizir Ferreira; Dos Santos, Júlio César (FapUNIFESP (SciELO), 2016)
A food grade lipase from Rhizopus oryzae immobilized on a hybrid polysiloxane-polyvinyl alcohol matrix (SiO2-PVA) was used as the biocatalyst to mediate the interesterification reactions of a blend containing 65% milkfat and 35% soybean oil. All the reactions occurred in an inert nitrogen atmosphere in cylindrical glass reactors (80 mL) with 40 g of the milkfat-soybean oil blend. The influence of the following variables was evaluated: biocatalyst loading (250-1500 activity units per gram of blend), biocatalyst moisture content (5-20%), temperature (45-60 °C) and incubation time (2-48 h). The reactions were monitored by determining the free fatty acid content, triacylglycerol (TAGs) composition in carbon species, and the consistency of the interesterified (IE) products. The reaction conditions were set based on the parameters that provided a high interesterification yield and good consistency of the final product within the ideal range (200 to 800 gf cm-2). Hence the best results were obtained using a biocatalyst loading of 500 U g-1 of blend with 10% moisture content at 45 °C for 4 h. Under these conditions the consistency of the interesterified product was 539.7 ± 38 gf cm-2. The results demonstrated the potential of the immobilized lipase to alter the TAGs profile of the milkfat-soybean oil blend, allowing for the production of structured lipids.
Keywords: Interesterification; Milkfat; Rhizopus oryzae lipase; Soybean oil